1993
DOI: 10.1038/ng1093-174
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of new mutations for Huntington's disease: intermediate alleles and sex of origin effects

Abstract: Huntington's disease (HD) is associated with expansion of a CAG repeat in a novel gene. We have assessed 21 sporadic cases of HD to investigate sequential events underlying HD. We show the existence of an intermediate allele (IA) in parental alleles of 30-38 CAG repeats in the HD gene which is greater than usually seen in the general population but below the range seen in patients with HD. These IAs are meiotically unstable and in the sporadic cases, expand to the full mutation associated with the phenotype of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
0
3

Year Published

1993
1993
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(118 citation statements)
references
References 22 publications
4
111
0
3
Order By: Relevance
“…Intermediate alleles (IAs), also known as large normal alleles, are between 27 and 35 CAG repeats and may give rise to de novo expansions on transmission. [4][5][6][7][8] Individuals with IAs will not develop HD, however, their offspring are at risk of inheriting a CAG tract that has expanded into the pathogenic range. Although the size of the CAG tract contributes to instability and is associated with age of onset, there is significant phenotypic variation among individuals with identical repeat lengths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermediate alleles (IAs), also known as large normal alleles, are between 27 and 35 CAG repeats and may give rise to de novo expansions on transmission. [4][5][6][7][8] Individuals with IAs will not develop HD, however, their offspring are at risk of inheriting a CAG tract that has expanded into the pathogenic range. Although the size of the CAG tract contributes to instability and is associated with age of onset, there is significant phenotypic variation among individuals with identical repeat lengths.…”
Section: Introductionmentioning
confidence: 99%
“…1,9 Various other factors, including non-CAG genetic modifiers, have been suggested to have a role in expansion and the age of onset of disease symptoms. 5,7,10 Several studies have attempted to make use of genome-wide analyses in order to identify genetic modifiers and better understand HD aetiology and pathogenesis. [11][12][13] A number of processes were implicated in early disease pathogenesis; however, specific genetic modifiers are still under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The HD mutation was found to be in linkage disequilibrium with 2 major haplotypes and also to be carried by a plethora of different haplotypes, indicating that new mutations do not constitute as rare an event as was previously thought (MacDonald et al, 1992). Indeed, new HD mutations have been documented by CAG typing (Myers et al, 1993;Goldberg et al, 1993). Several authors have pointed out that haplotypes overrepresented in HD are found in the normal population with repeat numbers at the upper end of the normal range (Squitieri et al, 1994;Almqvist et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this same gene configuration with SCA1, such alleles do not seem to be a pre-mutation because they distribute selectively at the lower limit of normal alleles. On the other hand, analysis of a new mutation in the HD gene strongly indicates that pre-mutation does occur from a pool of normal alleles with limited instability, but having repeats larger than those of typical normal alleles (Goldberg et aL, 1993). In SCA1, CAT interruption within the CAG repeat tract is considered to stabilize an SCA1 allele on replication .…”
Section: Discussionmentioning
confidence: 99%